Religion and female body in ancient Judaism and its environments - Xeravits, Géza G. (Boston : Walter de Gruyter, 2015)
"This volume publishes papers read at the ninth International Conference on the Deuterocanonical Books, Budapest, 2012. The authors explore various aspects of manifestations of the female principle within the literature of the Ancient Near East, Early Judaism, and the nascent Christianity"--
Includes bibliographical references and index.
Keywords: Bible. -- Criticism, interpretation, etc. -- Congesses; Bible. -- Criticism, interpretation, etc. -- Congresses; Women in the Bible -- Congresses; Human body in the Bible -- Congresses; Middle Eastern literature -- History and criticism -- Congresses; Frühjudentum.; Frau; Literatur; Körper.; Leiblichkeit; Gnosis; Alter Orient; Bible; Bible; Human body in the Bible; Middle Eastern literature; Women in the Bible; Conference papers and proceedings; Criticism, interpretation, etc